Valutare e certificare le competenze degli studenti nell'assolvimento dell'obbligo di istruzione. Un'indagine empirica nella scuola secondaria della Regione Abruzzo - Anna Maria Ciraci; Maria Vittoria Isidori; Claudio Massimo Cortellesi (LED Edizioni Universitarie, 2023)
ASSESS AND CERTIFY STUDENTS' SKILLS IN FULFILLING THE COMPULSORY EDUCATION. AN EMPIRICAL SURVEY IN SECONDARY SCHOOL OF THE ABRUZZO REGION Abstract The article concerns the results of an empirical investigation relating to evaluation practices and opinions of secondary school teachers in the Abruzzo Region on the evaluation and certification of skills in fulfilling compulsory education. To collect information, a questionnaire was administered to a sample of 383 teachers. After an initial descriptive analysis, some contingency tables were produced from which some statistically significant connections emerged. The preliminary results of the study highlight good practices in the management of evaluation processes, such as the use of evaluation as a resource for learning, but still show a lack of awareness of the difference between learning and transversal citizenship skills and a poor mastery of docimological tools capable to grasp the complexity that characterizes skills.